VD_FINDINFO Arrêt / 2011 / 904 vom 11. Juli 2011 - VD Tribunal cantonal (2011)
RETRAIT DU DROIT DE GARDE, CURATELLE ÉDUCATIVE, RELATIONS PERSONNELLES | 273 al. 1 CC, 308 al. 1 CC, 310 al. 1 CC, 315a al. 3 CC, 399 CPC, 489 CPC